Evaluating the process of mental health and primary care integration: The Vermont Integration Profile. Issue 1 (1st March 2015) - Kessler, Rodger
Abstract : Objective: We developed and tested a measure to identify level of primary care behavioral health integration. We produced a thirty item, six domain electronically delivered measure, and a total score. Methods: We generated a convenience sample of 137 survey responses, including 104 primary care practices. We provided each practice a summary of their own data, and generated a data base of all submissions. We calculated descriptive statistics. Results: The mean total score was 56/100. The Vermont Integration Profile (VIP) discriminated between types of practices in the direction hypothesized. Initial test retest reliability was good. Conclusion: The VIP demonstrated good feasibility and construct validity, initial reliability, low provider demand and good discrimination between types of practices.